[Aerial view of Cal Poly campus] (1975)
Aerial view of Cal Poly main campus, Poly "P", North Mountain, Red Brick Dormitories, Sierra Madre, Yosemite, Administration, University Union, Engineering East, Engineering West, Science Building, Dexter Library, Spanos Stadium, California Boulevard, Foothill Boulevard - looking east